Value Creation from Internationalization of Sugar Cane by-products: a multi-stakeholder view of artisanal cachaça production - Neutzling, Daiane Mulling (2015)
Objective – The aim of this paper was to identify the strategiesdeveloped for internationalization in order to create value in theartisanal cachaça sector of Brazil.Design/methodology/approach – A multiple-case study was appliedin two artisanal cachaçarias. we carried out in-depth, semi-structuredinterviews with different stakeholders involved in supportinginternationalization of these companies. To select the stakeholders weused snowball sampling. The content of the interviews was categorizedand analysed according to accepted theory.Findings – Our study provides an overview of the organization andstructure of the cachaçarias and reveals how internationalization isadding value to this network from a multi-stakeholder view. Thesupport of the multi-stakeholder network is in an early stage, butit offers a promising future, since there is a consumer market beingdeveloped. Political power is needed to regulate the industry.Practical implications – Business internationalization of thehandmade cachaça sector is a challenge, as most companies are smalland do not have adequate financial resources or proper knowledgeregarding international markets. Regulatory stakeholders support thecachaçarias in standardizing production and developing internationalstrategies. The results can help to better understand the importance ofcollaboration embedded in stakeholder network relationships.Originality/value – Empirical research on internationalization indeveloping countries, especially in small and mediums sized firms isstill very limited. We have shown that companies can benefit fromspecific organization structures when developing relationships withinmulti-stakeholder networks.